Analysis of good practices and perceptions of stakeholders to support the development of domestic markets - Prdić Nedeljko; Čavlin Miroslav; Kaiaman Nasser Khalifa (Ekonomija: teorija i praksa, 2023)
Intense competition and changes in the global market have also affected the markets, which are strategically being redirected to the sale of organic agricultural products and tourism using the traditional importance and position in the infrastructure of cities. The primary goal of the research is to create strategic guidelines for the development of markets in the Republic of Serbia, but based on the identification of globally competitive business examples and the views of management, sellers and buyers on the potential of domestic markets. The research methodology includes descriptive, quantitative and qualitative analysis that resulted in the presentation of effective business solutions on the global market and priorities for developing the potential of domestic markets. In addition, through a survey survey of the attitudes of the management of relevant market organizations, the motives and needs of reference sellers and buyers in the markets, the perception of key actors on the state and prospects of the domestic market business was ascertained. market of organic food and tourism, as well as the necessity of creating a national framework for the development of domestic markets. Therefore, the results of the conducted research can especially benefit the creators of local and national economic policy as an instrument in improving the business environment, and domestic market organizations and actors a better insight into the possibilities of using and developing potential.